Introduction to topological quantum computation - Pachos, Jiannis K. (Cambridge : Cambridge University Press, 2012)
'Combining physics, mathematics and computer science, topological quantum computation is a rapidly expanding research area focused on the exploration of quantum evolutions that are immune to errors. In this book, the author presents a variety of different topics developed together for the first time, forming an excellent introduction to topological quantum computation. The makings of anyonic systems, their properties and their computational power are presented in a pedagogical way. Relevant calculations are fully explained, and numerous worked examples and exercises support and aid understanding. Special emphasis is given to the motivation and physical intuition behind every mathematical concept. Demystifying difficult topics by using accessible language, this book has broad appeal and is ideal for graduate students and researchers from various disciplines who want to get into this new and exciting research field'--
Part I. Preliminaries: 1. Introduction; 2. Geometric and topological phases; 3. Quantum computation; 4. Computational power of anyons -- Part II. Topological Models: 5. Quantum double models; 6. Kitaev's honeycomb lattice model; 7. Chern-Simons quantum field theories -- Part III. Quantum Information Perspectives: 8. The Jones polynomial algorithm; 9. Topological entanglement entropy; 10. Outlook.
Includes bibliographical references (pages 197-203) and index.
Keywords: Quantum theory -- Data processing; Topology